COMPUTERIZATION OF PRIMARY HEALTH CARE INFORMATION SYSTEMS: ADVANCES AND CHALLENGES - Ricardo Bezerra Cavalcante; Daniela Dias Vasconcelos; Tarcísio Laerte Gontijo; Eliete Albano de Azevedo Guimarães; Richardson Miranda Machado; Valéria Conceição de Oliveira (Universidade Federal do Paraná, 2018)
Objective:to analyze the implantation of the e-SUS Primary Health Care strategy in the West Region of Minas Gerais, Brazil. Method:descriptive case study, with data from 62 people responsible for implementation in 54 municipalities, between May and June 2015, as well as two interviewees and analysis of the following documents: "Implantation of the e-SUS PHC in SRS Divinópolis" (Implantação do e-SUS AB na SRS Divinópolis)and "Municipalities, by Implantationof the e-SUS PHC in SRS Divinópolis" (Municípios por Situação de Implantação do e-SUS AB na SRS Divinópolis). The data were analyzed by descriptive statistics and Content Analysis, using the Atlas ti software, version 7.0. Results:in44(81.5%) of the municipalities, only the simplified data register was implemented, and 22 (40.7%)of the municipalities are in scenario three of implantation, 34 (54.8%) of those responsible for implantation are not permanently contracted staff. Conclusion:The implantation has weaknesses related to infrastructure and shortcomings in theprofessionals' training and resistance. It is necessary to review the planning of the implantation, taking its complexity into account.